Sustainable Future of Academic Libraries: Unveiling the Student Voice - Somaratna, Sajeewanie D.; Silva, M.A.L.; Adhikari, H.I.S.M. (University of Colombo, 2024)
Today, academic libraries are facing unprecedented challenges due to the vast availability of online information sources. The new generations of undergraduates, who are the main user group of academic libraries are highly tech-savvy and belong to the demographic cohort of digital natives. There is a dire need for academic libraries to evolve and adapt to the needs of new generations of users to thrive in the future. The objectives of the study are to identify library usage (2013-2023), underpinning reasons, and future expectations of undergraduates of the University of Colombo. It incorporates a qualitative research methodology and a single-site case study approach. This study consists of two phases. In phase 1, annual reports and other internal documents of the Library were analysed to determine the number of books borrowed during the period. In phase 2, in-depth interviews were conducted with undergraduates representing Level 1-4 from all the faculties served by the Main and Science Libraries. Twentyfour subjects were interviewed for a total of 8 hours until data saturation and analysis was conducted using the interpretive discourse analytical approach. Data obtained through ...
Keywords: Future Libraries; Student Voice; User Expectations; Sustainability